Kreativitas Lokal untuk Kemandirian Desa: Strategi Pengembangan Produk Unggulan Sukorejo - Choirun Nisak; Dies Nurhayati (Jurnal Pengabdian Masyarakat IPTEKS, 2025)
This study aims to analyze strategies for developing superior local products based on community potential in Sukorejo Village, Pohjentrek District, Pasuruan Regency. Sukorejo Village possesses diverse creative and socio-cultural economic potentials, including home industries such as embroidery, knitting, furniture production, and the making of Hajj caps, as well as the agricultural sector that applies the innovative jajar legowo planting system. In addition, the local cultural tradition Besaran, celebrated annually during Eid al-Adha, represents a form of collective solidarity and local wisdom that holds great potential as a cultural tourism attraction. Therefore, developing Sukorejos local potentials is considered a promising pathway to achieving rural independence and sustainable development. This research employed a qualitative method with a descriptive approach. Data were collected through in-depth interviews with the community leaders, local entrepreneurs, and farmer groups. The data were analyzed interactively through the stages of reduction, presentation, and conclusion drawing to describe the factual conditions of local potential management and development strategies. The findings reveal that Sukorejos creative economy is rooted in the communitys traditional skills and craftsmanship but has not yet been optimally managed due to limited innovation in design, digital promotion, and market access. The study concludes that Sukorejos success in achieving sustainable local development depends on cross-sector collaboration such synergy is essential to build a productive, competitive, and sustainable.